Navigating Get-Tough and Support-Oriented Philosophies for Improving School Safety: Insights from School Administrators and School Safety Staff - Collier, Nicole L. (American journal of criminal justice, 2019)
Schools in the United States are increasingly faced with the challenge of navigating two seemingly contradictory approaches to school safety. On the one hand, they attempt to make schools safer by employing get-tough, punishment-oriented policies. On the other hand, schools promote support-oriented policies that seek to address the root causes of students’ behavioral issues. Despite considerable advances in research on school safety, little is known about how schools balance the implementation of these two approaches. To address this research gap, we present findings from interviews with school principals, assistant principals, discipline coordinators, police, and district leaders to illustrate how schools navigate the implementation of these competing school safety philosophies. Implications for theory, research, and policy are discussed.